Quality assessment of past thermal upgrading projects and an attempt to classify characteristic problems using two-level thermography - Ostańska, Anna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
Two-stage thermography was used in this study. This means that thermograms in the first stage of thermographic research were made using air transport (helicopter tour of the housing estate). Then, after selecting thermally leaking buildings, in the second stage of thermographic research observations were made from the ground level (round and inspection of buildings elements selected in the first stage). The aim of infrared investigations, successively carried out from 2006 to 2020, was the current assessment of the quality of thermal insulation of multifamily buildings using a non-destructive method and an attempt to determine the necessary repair recommendations, which are aimed at elimination of the remaining or newly formed thermal leaks in the building shell and sustainable operation of the multifamily building. The article presents the results of thermographic tests and proposes three ways of analysis (preliminary, quality and statistical).